Effectiveness of Visual Inspection with Acetic Acid versus Papanicolaou Smear for Cervical Cancer Screening at Kirtipur Hospital - Pradhan, Peru; Shrestha, Sona; Dangal, Ganesh; Bhattachan, Kabin (Nepal Journal of Obstetrics and Gynaecology, 2017)
Aims: The aim of this study was to compare the accuracy of detecting precancerous cervical cells, via a visual inspection of the cervix and an application of acetic acid (VIA) with the Papanicolaou (Pap) smear,to screen for cervical cancer in resource poor countries. Methods: The study involved 189 women between the ages of 30-60 years, who attended the Gynaecological Out Patient Department at Kirtipur hospital from 1st December 2014 to 31st March 2015. A VIA and Pap smear was done in all women, with cervical biopsies conducted in VIA positive women. Results: Themajority of these women were in the age range of 30-39 years, non-smokers, housewives, multipara and non-users of contraception. Of the tested group 8 (4.2%) had a history of post coital bleeding, 64 (21.2%) presented with lower abdominal pain, 64 (33.9%) presented with suspected abnormal vaginal discharge and 34 (17.98%) with dysfunctional uterine bleeding. Out of 189 women the VIA was positive in 5 (2.62%) and a Pap smear was positive in 2 (1.1%). Bycomparison to a Pap smear the VIA has an accuracyof 100%, specificity 98.4%, positive predictive value 40% and negative predictive value 100%. Conclusions: A visual inspection of the cervix with acetic acid performed by a qualified physician is a suitable alternative for precancerous cell screening in low resource settings.